2016
DOI: 10.1530/rep-15-0397
|View full text |Cite
|
Sign up to set email alerts
|

CXADR is required for AJ and TJ assembly during porcine blastocyst formation

Abstract: Coxsackie virus and adenovirus receptor (CXADR) is a member of the immunoglobulin superfamily as well as a member of the junctional adhesion molecule family of adhesion receptor. In human pre-implantation embryos, CXADR was detected and co-localized with tight junction (TJ) proteins on the membrane of the trophectoderm. However, its physiological roles were not elucidated in terms of blastocyst formation. Here, we reported expression patterns and biological functions of CXADR in porcine pre-implantation embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…In early mammalian embryos, including humans, mice, and pigs, coxsackievirus and adenovirus receptor (CXADR) is found at the apical contacts of the TE and endometrial epithelium, suggesting that CXADR might be involved in establishing the trophoblast and in further development (B. Choi, Nah, Oh, Gye, & Kim, ; Krivega, Geens, & Van de Velde, ; Kwon et al, ). To investigate the effects of depleting Cxadr on pre‐ and peri‐embryo development, we expand our previous findings (Kwon et al, ; Kwon et al, ) in which porcine CXADR is involved in adherens junction (AJ)/TJ formation and interacts with ADAM10 and TJP1 for TJ assembly during preimplantation development. We first examined preimplantation developmental competency by deleting components of the TJ complex by injecting Cxadr or A disintegrin and metalloproteinase 10 (Adam10) small interfering RNA (siRNA), respectively, and disrupted/inhibited the TJ complex using an Adam10 chemical inhibitor (GI254023X).…”
Section: Introductionmentioning
confidence: 99%
“…In early mammalian embryos, including humans, mice, and pigs, coxsackievirus and adenovirus receptor (CXADR) is found at the apical contacts of the TE and endometrial epithelium, suggesting that CXADR might be involved in establishing the trophoblast and in further development (B. Choi, Nah, Oh, Gye, & Kim, ; Krivega, Geens, & Van de Velde, ; Kwon et al, ). To investigate the effects of depleting Cxadr on pre‐ and peri‐embryo development, we expand our previous findings (Kwon et al, ; Kwon et al, ) in which porcine CXADR is involved in adherens junction (AJ)/TJ formation and interacts with ADAM10 and TJP1 for TJ assembly during preimplantation development. We first examined preimplantation developmental competency by deleting components of the TJ complex by injecting Cxadr or A disintegrin and metalloproteinase 10 (Adam10) small interfering RNA (siRNA), respectively, and disrupted/inhibited the TJ complex using an Adam10 chemical inhibitor (GI254023X).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that CXADR (coxsackie virus and adenovirus receptor), a member of the junctional adhesion molecule (JAM) family of adhesion receptors, is necessary for the assembly of adherens junction (AJ) and tight junction (TJ) proteins during porcine preimplantation embryo development [ 1 ]. Interestingly, the CXADR knockdown (KD) study showed that CXADR plays critical roles in porcine embryo compaction and cavitation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that CXADR (coxsackie virus and adenovirus receptor), a member of the junctional adhesion molecule (JAM) family of adhesion receptors, is necessary for the assembly of adherens junction (AJ) and tight junction (TJ) proteins during porcine preimplantation embryo development [ 1 ]. Interestingly, the CXADR knockdown (KD) study showed that CXADR plays critical roles in porcine embryo compaction and cavitation [ 1 ]. In line with previous studies [ 2 ], our recent finding provides clear evidence that CXADR is a component of TJ assembly and is essential for paracellular sealing on trophectoderm (TE) epithelial cells during blastocyst development [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study is to investigate the effect of defects of TJ complex/integrity on postimplantation embryo development and to expand our previous findings (Kwon et al, 2016a;Kwon et al, 2016b;Jeong et al, 2019) where CXADR interacts with ADAM 10 and they are required for AJ/TJ assembly during preimplantation development in pig and mouse. In line with previous studies (Kwon et al, 2016a;Kwon et al, 2016b;Jeong et al, 2019), we found that depletion of Cxadr and inhibition of 2006). Thus, the gradual weight gain after ET may reflect increased embryo and placental weight, but weight-loss for two consecutive days is attributed to loss of embryos because maternal body weight rapidly increased from around 2nd trimester onwards (Kulandavelu et al, 2006).…”
Section: Resultsmentioning
confidence: 97%
“…The significance of tight intersection (TJ) and cavitation during preimplantation embryo development have been featured since McLaren and Smith's pioneer work (McLaren and Smith 1977). Recent studies revealed that Tfap2c is a core key transcription factor for establishment of TJ complex in mouse models, and identified other constituents involved in TJ assembly during preimplantation (Choi et al, 2012;Kwon et al, 2016a;Kwon et al, 2016b). In addition, we reported that complex of coxsackievirus and adenovirus receptor (Cxadr) and A disintegrin and metalloproteinase 10 (Adam10) play pivotal roles in TJ integrity/stability and early trophoblast development in mouse.…”
Section: Introductionmentioning
confidence: 99%